The threat of zero‐dynamics attack on non‐linear cyber‐physical systems - Amir Norouzi Mobarakeh; Mohammad Ataei; Rahmat‐Allah Hooshmand (IET Cyber-Physical Systems)
Abstract Zero‐dynamics attack (ZDA) is a destructive stealthy cyberattack that threatens cyber‐physical systems (CPS). The authors have warned about the risk of a cyberattack by introducing a new general ZDA that can be effective and robust in non‐linear multiple‐input multiple‐output CPS. In this proposed attack policy, the adversary extracts the sensor and actuator online data on the network platform. Then, by utilising a state observer and considering specific delay times, the attacker injects a ZDA signal into the actuator channels of the cyber‐physical system. As a result, the internal dynamics will diverge from the nominal working region of the controlled cyber‐physical system, while the outputs remain close to the actual outputs of the attack‐free system. Therefore, this cyberattack can remain stealthy, and it can also be robust against revealing signals. The efficiency of this new attack policy is demonstrated in the simulation results for a continuous stirred tank reactor regarded as a cyber‐physical system.